Observation of adhesive force and energy of adsorbents on rubber substrates by atomic force microscopy. (16th May 2014) - Lee, Nuri; Jo, W.; Lee, B. K.; Jung, W. K.
<x xml:space="preserve">Abstract</x> We observed the surface morphology and adhesive interaction of adsorbents on rubber substrates by atomic force microscopy (AFM). The detachment of adsorbents from rubber substrates is an important issue for various machines like home appliances and laundry machine. Since a clean surface of the functioning parts is required, a frequent cleaning process must be developed. In particular, dust and lint have a tendency to bind to the rubber surface of a laundry machine. Several practical methods have been attempted to remove these particles from the surface. Pure water, detergent, sodium hypochlorite (65 °C), and cold water (18 °C) are treated onto artificial dust and lint mixtures on rubber with water fluid by rapid rpm. The dust‐and‐lint adsorbents are investigated by AFM after the treatment, and topographic images and force–distance (F–D) curves were generated for the samples. The roughness, measured as the root mean square, is a key factor to judge the cleaning quality. From the F–D curves, we are able to obtain adhesive energy in addition to adhesive force which will yield qualitative measures of the interactions between the remaining adsorbents and the rubber surface. Considering the values that were measured, hot water with water fluid by rapid rpm offers the best performance when cleaning the surface. The chemical like sodium hypochlorite is good for thinning the materials, but it solidifies them, which is eventually detrimental to proper functioning. Copyright © 2014 John Wiley & Sons, Ltd.